HEMATOLOGIC VALUES, BILIRUBIN AND ENZYME ACTIVITIES IN SERUM OF PERUVIAN PASO HORSES FROM LURIN VALLEY, LIMA - Díaz G., Henry (2011)
The hematological and blood biochemical parameters are useful tools for equinemedical practice but their usefulness for the Peruvian Paso Horse is limited by the absenceof reference values. The present study was conducted to determine hemato-biochemicalvalues in apparently healthy horses. Forty nine animals were evaluated and they were classified according to sex [males (n=17), females (n=30)] and age [young (n=23), adults(n=26)]. The hematological (red blood cell count, hematocrit, hemoglobin concentration,mean corpuscular volume, mean corpuscular hemoglobin concentration, white blood cellcount, band neutrophils, segmented neutrophils, eosinophils, monocytes, lymphocytes,neutrophil/lymphocyte ratio and platelet count) and the biochemical (total bilirubin, directbilirubin, indirect bilirubin, ALT, AST, ALP, GGT and CK) profiles were estimated bymeans of automated analyzers. The effect of sex and age was evaluated. Sex influencedthe number of monocytes and CK activity, and age influenced hemoglobin concentration,mean corpuscular volume, mean corpuscular hemoglobin concentration, lymphocytes,neutrophil/lymphocyte ratio, ALT, AST, total bilirubin and indirect bilirubin (p<0.05).